Rapamycin as an Adjunctive Therapy for NLRC4 Associated Macrophage Activation Syndrome - Barsalou, Julie; Blincoe, Annaliesse; Fernandez, Isabel; Dal-Soglio, Dorothée; Marchitto, Lorie; Selleri, Silvia; Haddad, Elie; Benyoucef, Aissa; Touzot, Fabien (Frontiers in Immunology, 2018)
Gain of function (GOF) mutations affecting the inflammasome component NLRC4 are known to cause early-onset macrophage activation syndrome (MAS) and neonatal enterocolitis. Here we report a patient with a NLRC4 GOF mutation presenting with neonatal MAS efficiently treated with a combination of anakinra and rapamycin. Through in vitro studies, we show that rapamycin reduces both IL-1β and IL-18 secretion by the patient’s phagocytic cells. The reduction of cytokine secretion is associated with a reduction of caspase-1 activation regardless of the pathogen- or danger-associated molecular patterns triggering the activation of the inflammasome. This study suggests that patients with inherited auto-inflammatory disorders could benefit from an adjunctive therapy with rapamycin.